Prevalence of pneumonia and its associated factors among under-five children in East Africa: a systematic review and meta-analysis - Biruk Beletew; Melaku Bimerew; Ayelign Mengesha; Mesfin Wudu; Molla Azmeraw (BMC, 2020)
Abstract Background Pneumonia is defined as an acute inflammation of the Lungs' parenchymal structure. It is a major public health problem and the leading cause of morbidity and mortality in under-five children especially in developing countries. In 2015, it was estimated that about 102 million cases of pneumonia occurred in under-five children, of which 0.7 million were end up with death. Different primary studies in Eastern Africa showed the burden of pneumonia. However, inconsistency among those studies was seen and no review has been conducted to report the amalgamated magnitude and associated factors. Therefore, this review aimed to estimate the national prevalence and associated factors of pneumonia in Eastern Africa Methods Using PRISMA guideline, we systematically reviewed and meta-analyzed studies that examined the prevalence and associated factors of pneumonia from PubMed, Cochrane library, and Google Scholar. Heterogeneity across the studies was evaluated using the Q and the I2 test. A weighted inverse variance random-effects model was applied to estimate the national prevalence and the effect size of associated factors. The subgroup analysis was conducted by country, study design, and year of publication. A funnel plot and Egger's regression test were used to see publication bias. Sensitivity analysis was also done to identify the impact of studies. Result A total of 34 studies with 87, 984 participants were used for analysis. The pooled prevalence of pneumonia in East Africa was 34% (95% CI; 23.80-44.21). Use of wood as fuel source (AOR = 1.53; 95% CI:1.30-1.77; I2 = 0.0%;P = 0.465), cook food in living room (AOR = 1.47;95% CI:1.16-1.79; I2 = 0.0%;P = 0.58), caring of a child on mother during cooking (AOR = 3.26; 95% CI:1.80-4.72; I2 = 22.5%;P = 0.26), Being unvaccinated (AOR = 2.41; 95% CI:2.00-2.81; I2 = 51.4%;P = 0.055), Child history of Acute Respiratory Tract Infection (ARTI) (AOR = 2.62; 95% CI:1.68-3.56; I2 = 11.7%;P = 0.337) were identified factors of pneumonia. Conclusion The prevalence of pneumonia in Eastern Africa remains high. This review will help policy-makers and program officers to design pneumonia preventive interventions.